The Role of Organizational Culture in Developing Professional Capabilities in Makkah Al-Mukarramah Department of Education (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the reality of organizational culture and the level of professional capacity development within the Education Administration of Makkah City from the perspective of its employees. It also sought to uncover statistically significant differences in participants’ responses regarding organizational culture and professional capacity levels based on gender, job position, and years of experience. Additionally, the study aimed to determine the nature of the relationship between organizational culture and the level of professional capacity development in the Makkah Education Administration from the employees’ point of view, and to achieve the study’s objectives, the researcher adopted a descriptive correlational methodology, relying on a questionnaire as the main data collection tool. The study population consisted of all male and female employees at the Makkah Education Administration, totaling (719) employees. A random sample of (257) employees was selected, the results indicated that the overall mean score for organizational culture among employees in the Makkah Education Administration was (3.53), indicating a high level of response. The overall mean score for professional capacities was (3.71), also reflecting a high response level. The findings revealed no statistically significant differences in participants' responses regarding organizational culture as a whole based on gender or job position. However, statistically significant differences were found based on years of experience, favoring employees with 10 years or more of experience, particularly those with 15 years or more. Furthermore, the results showed no statistically significant differences in responses regarding the level of professional capacities based on gender, job position, or years of experience, the study also found a positive correlation between organizational culture and the development of professional capacities among employees in the Makkah Education Administration, In light of the results, the researcher recommended adopting both material and moral incentive programs to encourage employee creativity and innovation, and to strengthen a culture of excellence and quality among staff within the Education Administration.
Keywords: Organizational culture; Professional capacities